Virtual Sport Event Activities During Pandemic - Aprilia, Hervina Dyah (Bina Nusantara University, 2022)
The main objective of this study is to analyse the experiences of visitors and participants in accessing the virtual exhibition at the VR Duathlon Series TOBA 2020, which was taken place on September 26, 2020, at a location around Lake Toba, North Sumatra. This sports event is routinely held every year in different locations. However, it was carried out online during this pandemic to implement several activities such as exhibition information, competition activities, and tourism through virtual media. This research on virtual exhibitions completed using quantitative methods of analysing virtual reality from virtual reality application at sports events—the quantitative methods used by surveying 102 participants who accessed the virtual exhibition at the sporting event. This study stated that the completeness of the information regarding competition and tourism activities and the visual appearance of the environment from the virtual exhibition had a considerable influence on participants who accessed the virtual exhibition. The participants who access the virtual exhibition shown a desire to visit the event location after accessing the online virtual exhibition. This result answers the question that the application of virtual reality in sports events can provide a different experience for participants accustomed to attending events offline but need a more realistic virtual appearance to simulate the environment where the event took place as a visual and tourism attraction.